2014
DOI: 10.4236/crcm.2014.37096
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Adenoid Cystic Carcinoma of the Breast: Discussion and Review of the Literature

Abstract: Adenoid cystic carcinoma (ACC) of the breast is a rare type of primary breast cancer with a favorable prognosis, despite its triple-negative status. There has been no consensus regarding treatments. We will report a case of Adenoid cystic carcinoma of the breast presented with localized disease and no axillary lymph node metastases. We performed a radical mastectomy with axillary lymph node dissection, with a favorable clinical course and we will describe the clinic pathologic features of ACC of the breast and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Studies have shown it to be low grade, node negative and receptor negative tumour [49] and one of the only triple negative cancers where there is no role for chemotherapy [50] . Although, lymph node involvement in breast ACC is uncommon [45,47,51] , some surgeons still prefer to perform sampling of nodes as seen in both our cases. As this condition is rare, we are unable to not recommend axillary procedures due to the diversity of procedures offered.…”
Section: Adenoid Cystic Carcinomamentioning
confidence: 80%
See 4 more Smart Citations
“…Studies have shown it to be low grade, node negative and receptor negative tumour [49] and one of the only triple negative cancers where there is no role for chemotherapy [50] . Although, lymph node involvement in breast ACC is uncommon [45,47,51] , some surgeons still prefer to perform sampling of nodes as seen in both our cases. As this condition is rare, we are unable to not recommend axillary procedures due to the diversity of procedures offered.…”
Section: Adenoid Cystic Carcinomamentioning
confidence: 80%
“…Due to the rarity of this condition no definite surgical treatment is recommended. There are studies supporting simple lumpectomy with or without radiation, simple to radical to mastectomy [47] . The chance of local recurrence has been high.…”
Section: Adenoid Cystic Carcinomamentioning
confidence: 99%
See 3 more Smart Citations